Glycolipid binding preferences of Shiga toxin variants. - Sayali S Karve; Alison A Weiss (PLoS ONE, 2014)
The major virulence factor of Shiga toxin producing E. coli, is Shiga toxin (Stx), an AB5 toxin that consists of a ribosomal RNA-cleaving A-subunit surrounded by a pentamer of receptor-binding B subunits. The two major isoforms, Stx1 and Stx2, and Stx2 variants (Stx2a-h) significantly differ in toxicity. The exact reason for this toxicity difference is unknown, however different receptor binding preferences are speculated to play a role. Previous studies used enzyme linked immunosorbent assay (ELISA) to study binding of Stx1 and Stx2a toxoids to glycolipid receptors. Here, we studied binding of holotoxin and B-subunits of Stx1, Stx2a, Stx2b, Stx2c and Stx2d to glycolipid receptors globotriaosylceramide (Gb3) and globotetraosylceramide (Gb4) in the presence of cell membrane components such as phosphatidylcholine (PC), cholesterol (Ch) and other neutral glycolipids. In the absence of PC and Ch, holotoxins of Stx2 variants bound to mixtures of Gb3 with other glycolipids but not to Gb3 or Gb4 alone. Binding of all Stx holotoxins significantly increased in the presence of PC and Ch. Previously, Stx2a has been shown to form a less stable B-pentamer compared to Stx1. However, its effect on glycolipid receptor binding is unknown. In this study, we showed that even in the absence of the A-subunit, the B-subunits of both Stx1 and Stx2a were able to bind to the glycolipids and the more stable B-pentamer formed by Stx1 bound better than the less stable pentamer of Stx2a. B-subunit mutant of Stx1 L41Q, which shows similar stability as Stx2a B-subunits, lacked glycolipid binding, suggesting that pentamerization is more critical for binding of Stx1 than Stx2a.